The Mediating Influence of Brand Trust, Perceived Quality, and Brand Love on Brand Loyalty - Galuh Mira Saktiana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The competitive market for traditional food brands underscores the need to understand factors driving consumer loyalty. This study examines how brand experience influences brand loyalty, mediated by brand trust, perceived quality, and brand love. The objective is to clarify the mediating roles of these variables and address inconsistencies in prior research regarding their impact on loyalty for traditional food products. A quantitative cross-sectional design was employed, collecting data from 364 respondents using a purposive sampling method. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results show that brand experience does not directly affect brand loyalty, but significantly influences brand trust, perceived quality, and brand love, which in turn drive loyalty. Brand trust, perceived quality, and brand love partially mediate the relationship between brand experience and loyalty, with consumers favoring innovative flavors and cultural appeal. This study concludes that fostering trust, quality perceptions, and emotional attachment is crucial for building loyalty to traditional food, offering practical strategies for traditional brands to enhance consumer retention in competitive markets.